Phenomenes of Violence Women And Children - Pudentiana Rr; Ngatemi Ngatemi (Conference Series, 2020)
Violence is a term that is full of meaning "suffering", both from the perspective of psychological and legal, in which contained human behavior (person / group of people) that can cause suffering for others, (person / group). This library research aims to find out the phenomenon of violent behavior against women and children who recently - often a topic of conversation in various media due to the frequent various events in Indonesia. In relation to the matter, the importance of profession of Lecturers takes the role and function of the nation concern as well as continues to inspire every individual to be aware of the concepts, terminology of violent behavior, etiology, impact, prevention and prevention at least in the sphere of their respective families before the problem becomes more widespread and complex .